How do trees respond to species mixing in experimental compared to observational studies?. Issue 19 (10th September 2019) - Kambach, Stephan; Allan, Eric; Bilodeau‐Gauthier, Simon; Coomes, David A.; Haase, Josephine; Jucker, Tommaso; Kunstler, Georges; Müller, Sandra; Nock, Charles; Paquette, Alain; van der Plas, Fons; Ratcliffe, Sophia; et al.
Abstract: For decades, ecologists have investigated the effects of tree species diversity on tree productivity at different scales and with different approaches ranging from observational to experimental study designs. Using data from five European national forest inventories (16, 773 plots), six tree species diversity experiments (584 plots), and six networks of comparative plots (169 plots), we tested whether tree species growth responses to species mixing are consistent and therefore transferrable between those different research approaches. Our results confirm the general positive effect of tree species mixing on species growth (16% on average) but we found no consistency in species‐specific responses to mixing between any of the three approaches, even after restricting comparisons to only those plots that shared similar mixtures compositions and forest types. These findings highlight the necessity to consider results from different research approaches when selecting species mixtures that should maximize positive forest biodiversity and functioning relationships. Abstract : Using data from five European national forest inventories, six tree species diversity experiments, and six networks of comparative plots, we confirmed a general positive of species mixing on tree growth. Species‐specific responses to mixing were inconsistent between any of the tree approaches, even after restricting comparisons to only those plots that shared similar mixtures compositions and forest types. We thereby highlight the necessity to consider results from different research approaches to select species mixtures for maximizing biodiversity effects on tree growth.